The Effects of Feedback on Children's Engagement and Learning Outcomes in Robot-Assisted Second Language Learning - de Haas, Mirjam; Vogt, Paul; Krahmer, Emiel (Frontiers in Robotics and AI, 2020)
To investigate how a robot's use of feedback can influence children's engagement and support second language learning, we conducted an experiment in which 72 children of five years old learned 18 English animal names from a humanoid robot tutor in three different sessions. During each session, children played 24 rounds in an "I spy with my little eye" game with the robot, and in each session the robot provided them with a different type of feedback. These feedback types were based on a questionnaire study that we conducted with student teachers and the outcome of this questionnaire was translated to three within-design conditions: preferred feedback, dispreferred feedback, and no feedback. During the preferred feedback session, among others, the robot varied his feedback and gave children the opportunity to try again (e.g., `Well done! You clicked on the horse.', `Too bad, you pressed the bird. Try again. Please click on the horse.'); during the dispreferred feedback the robot did not vary the feedback (`Well done!', `Too bad.') and children did not receive an extra attempt to try again; and during no feedback the robot did not comment on the children's performances at all. \textcolor{red}{We measured the children’s engagement with the task and with the robot as well as their learning gain, as a function of condition. Results show that children tended to be more engaged with the robot and task when the robot used preferred feedback than in the two other conditions. However, preferred or dispreferred feedback did not have an influence on learning gain.} Children learned on average the same number of words in all conditions. These findings are especially interesting for long-term interactions where engagement of children often drops. Moreover, feedback can become more important for learning when children need to rely more on feedback, for example, when words or language constructions are more complex than in our experiment. The experiment’s method, measurements and main hypotheses were preregistered.